Analisis Fundamental Perusahaan dan Penilaian Intrinsik Saham sebagai Dasar Keputusan Investasi - Puspakaritas, Ferdiana Nur; Rusdianto, R Y (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Investment is a channel funds for future profits for investors. However, investment also has the risk of loss, so investors must be careful. During the Covid-19 pandemic, the economy had declined, as well as the IHSG. At that time, many companies in various sectors also experienced turmoil and decreased performance, one of which was in the property and real estate sector. Knowing this, it is important for investors to analyze the company's performance and shares before making investment decisions to avoid the risk of loss. The purpose of this study is to determine the performance and condition of the company's shares. The research sample is in the form of financial reports for the 2018-2022 period from 8 property and real estate companies. The analysis in this study uses financial ratios. Current ratio, earnings per share, return on equity, debt to equity ratio, total asset turnover, and dividend payout ratio are used to analyze company fundamentals, while price earning ratio and price to book value are used for intrinsic stock valuation. The results showed that 8 property and real estate companies had good performance. Based on the PER assessment at the end of 2022, many of the company's shares are undervalued, which is worth buying, while the PBV assessment shows that MKPI, DMAS, and PBSA shares are overvalued, which is worth selling.